Analysis of the fecal microbiome and metabolome in dairy cows with different body condition scores - Bhuripit Saraphol; Woranich Hinthong; Peerut Chienwichai; Natapol Pumipuntu; Onrapak Reamtong; Thassanee Srisook; Jiraphan Premsuriya (PLoS ONE, 2025)
Holstein Friesian is the most popular breed of dairy cows worldwide due to its exceptional milk production capabilities. In dairy cow management, the body condition score (BCS) is a useful tool, serving as a reliable indicator of a cow’s nutritional status and overall health. It is determined via a subjective visual and tactile assessment of fat cover and muscle mass. A low BCS is associated with decreased milk production and fertility. While genetic and nutritional factors have previously been associated with BCS, their effects are often moderate. In this study, we compared the fecal microbiome and the untargeted fecal metabolome of normal (BCS ≥  3, n =  16) and thin (BCS <  3, n =  16) Holstein Friesian dairy cows. The 16S rRNA gene-based metagenomic analysis revealed that thin cows had significantly higher levels of Clostridiaceae, Erysipelotrichales, Erysipelotrichaceae, and Turicibacter, while normal cows had higher levels of Clostridiales_vadinBB60_group, UCG-010, Bacteroidaceae, Ruminococcaceae, Paludibacteraceae, Alistipes, and Bacteroides. The fecal metabolomic analysis showed that key signaling pathways, including the mechanistic target of rapamycin (mTOR), phosphatidylinositol 3-kinase (PI3K)-Akt, and AMP-activated protein kinase (AMPK) pathways, were enriched in thin cows. In addition, a significant correlation was observed between differential microbial taxa and metabolites. Notably, Clostridiaceae and Erysipelotrichaceae species are linked to inflammation, infectious diseases, and conditions such as ruminal acidosis. Additionally, the mTOR, PI3K-Akt, and AMPK pathways are known to be activated by both nutrient deficiencies and inflammation. We propose that, in addition to genetic and nutritional factors, gut microbiome dysbiosis may contribute to subclinical health conditions, such as chronic inflammation and acidosis, which indirectly affect the cow’s BCS. These findings are guiding our ongoing research on the underlying health conditions in thin cows to better understand the role that the gut microbiome plays in the regulation of the body condition.